A comprehensive study of the whole profiles of short-chain fatty acids in milk - Xufang Wu; Fengen Wang; Meiqing Chen; Yingjie Qi; Lin Song; Nan Zheng; Jiaqi Wang; Yangdong Zhang (Journal of Dairy Science)
ABSTRACT: Although milk contains low levels of short-chain fatty acids (SCFA), these levels are higher than in plant oils and still exhibit significant biological activity. However, data regarding SCFA in milk are limited and fragmented. Therefore, our study used a laboratory-established method to analyze the SCFA profiles of milk from different species, geographical regions, and heat treatments. Our results revealed that SCFA composition of milk from Holstein cow, buffalo, ewe, and goat differs markedly from that of human, camel, and donkey, with camel and donkey displaying relatively similar SCFA composition. Furthermore, significant variations in SCFA content and composition were observed among different geographical regions. Additionally, significant volatilization losses of SCFA were noted due to the heat treatment of UHT sterilization (137°C for 4 s). Overall, species were found to be the major factor influencing total SCFA. This study provides substantial data to support a comprehensive investigation into the content and composition of SCFA in milk.